Aiming For The Future Of Bibliometric Forecast Research In Fraud Prevention: A Review Of Digital Economy Exploration - Bahrul, Bahrul; Fitriana, Fitriana; Santoso, Rachmat Agus (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This study aims to analyze and map the main research streams, research development, and further research directions in fraud prevention studies systematically. Using bibliometric analysis to analyze fraud prevention articles in the Scopus database based on preliminary data from 1985-2022 where there are 772 documents processed through VOSviewer software version 1.6.19. The study concluded that fraud prevention is a topic of international interest. Article by Rezaee. (2005), and an article in the Managerial Auditing Journal. Certain keywords, such as whistleblowing system, culture, management integrity, reputation, and blockchain technology provide a potential focus for future research.